2006
DOI: 10.1007/s00586-006-0089-9
|View full text |Cite
|
Sign up to set email alerts
|

C3-6 laminoplasty takes over C3-7 laminoplasty with significantly lower incidence of axial neck pain

Abstract: Five-lamina (C3-7) procedure is the most popular cervical laminoplasty and there have been no studies on the most appropriate number of laminae to be opened. We prospectively reduced the range of laminoplasty from C3-7 to C3-6 in 2002 and compared the outcome of C3-6 laminoplasty (n=37) to that of C3-7 laminoplasty (n=28). In both groups, neurological gain was satisfactory, radiographic changes were minimal, and postoperative MRI indicated sufficient expansion of the dura and the spinal cord. Average operating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
141
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 124 publications
(155 citation statements)
references
References 15 publications
(17 reference statements)
4
141
2
Order By: Relevance
“…Sakaura et al [34] found that the muscles at the cervicothoracic junction around the C7 spinous process played a central role in the development of this postoperative axial pain. Consequently, axial pain inherent in laminoplasty was reported to be reduced by preserving the C7 spinous process and its muscle and ligament attachments [6,7,32,42]. Furthermore, Hosono et al [9] revealed that C7, rather than the deep extensor muscles, was significantly related to axial pain.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Sakaura et al [34] found that the muscles at the cervicothoracic junction around the C7 spinous process played a central role in the development of this postoperative axial pain. Consequently, axial pain inherent in laminoplasty was reported to be reduced by preserving the C7 spinous process and its muscle and ligament attachments [6,7,32,42]. Furthermore, Hosono et al [9] revealed that C7, rather than the deep extensor muscles, was significantly related to axial pain.…”
Section: Discussionmentioning
confidence: 99%
“…These modifications aim at protecting the muscular attachment to spinous process and reconstruct the posterior structures. The reconstructive techniques [7,22,31,32,39,41,47] include reattachment of the spinous processes and musculatures, and preservation of deep extensor muscles and C2 or C7 spinous processes. Clinical studies have showed the advantages of these techniques over open-door laminoplasty in reducing axial pain and increasing cervical physiological lordosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations